(untitled) (Global Journal of Human-Social Science, 2023)
Exciting new studies in human evolution are appearing rapidly transforming scientific understanding of how the human community took form A 2018 article by archaeologist Eleanor Scerri and colleagues for example identifies key debates on this topic They ask When and how did Homo sapiens become a species How important were subgroups and migration in human evolution And while Scerri cannot yet propose a specific date or place for the origin of Homo sapiens she reveals certain misunderstandings in earlier thinking about human populations then points to new directions in interpretation Scerri argues that paleontology shows varied physical populations with varied material culture geographically spread through Africa She notes genetic evidence suggesting that the lineage for Homo sapiens traces back to 500 ka where ka in this essay means thousand years ago she also suggests human admixture with other hominin populations in Africa